Incisional Site Metastasis in a Patient with Cervical Carcinoma: A Case Report and Review of the Literature - C. Iavazzo; K. Madhuri; A. Tailor; S. Butler-Manuel (Case Reports in Obstetrics and Gynecology)
Abdominal wall metastasis either incisional, drain, or port is rather rare in patients treated for cervical carcinoma. We present a case of a patient who underwent an abdominal radical hysterectomy for a moderately differentiated cervical adenocarcinoma stage Ib1 and presented an incisional site metastasis 36 months after her operation. Moreover, we performed a literature search for abdominal wall metastases after radical hysterectomy for cervical cancer, and we present a table of the relative case reports. After our literature search, we clarified that the median time of recurrence was 14 months (range 1.5 month to 45 months). Thirty-three out of 42, 8/42, and 1/42 were squamous, adeno-, and adenosquamous carcinomas, respectively. Wide excision was performed in 30/37 cases of which we have information regarding the treatment option, while 11/37 and 13/37 underwent radiotherapy and chemotherapy, respectively. The possible mechanism of such a metastasis as well as the treatment options is discussed.